Effect of steel fibers on static and blast response of high strength concrete. (September 2017) - Luccioni, B.; Isla, F.; Codina, R.; Ambrosini, D.; Zerbino, R.; Giaccio, G.; Torrijos, M.C.
Highlights: Blast tests with different scale distances and contact explosions are reported. Effect of hooked end steel fibers on static and blast behavior of HSFRC is analyzed. Fiber addition can change response and type of failure of HSC under blast loads. Hooked end steel fibers help controlling flexure cracks, erosion and spalling. The improvements in flexural response are more important than in spalling control. Abstract: The advantages of High Strength Fiber Reinforced Concrete (HSFRC) in static behavior highlighted by many researchers suggest it is a promising material to withstand dynamic loads. However, available experimental results regarding blast performance of HSFRC structural elements are still limited. The results of exploratory series of tests using a high strength concrete, over 100 MPa compressive strength, reinforced with long hooked-end steel fibers are presented in this paper. The results of static characterization tests performed on prisms and slabs and the results of blast tests on slabs are presented and analyzed. The improvements found in static flexure response with different fibers contents are compared with those found under blast loads. The effects of fibers controlling cracking, scabbing and spalling under close-in explosions are also addressed.